A propósito de la elección en Tomás de Aquino - Anchepe, Ignacio Miguel (Sapientia, 2012)
The aim of this paper is to consider some topics of Thomistic philosophy of action regarding the issue of the electio, which is an elicit act of will that Aquinas develops in S.Th. 1-2.13 and elsewhere in his work. Unlike other interpretations, I will argue that the choice (at least as it was conceived by Thomas Aquinas) cannot be understood unless the voluntary component is emphasized, i.e., that the choice itself is inserted into a practical order specifically conceived as such. In other words, I will argue that human choice cannot be satisfactorily interpreted as the result of a simple expansion of practical reason, for human choices are much more than a simple motion activated by the appetitive practical judgment resulting from the rational deliberation. This paper is divided into four sections: first, by way of introduction, I will present an outline of Thomistic concept of choice and its Aristotelian background; secondly, I will expose two recent interpretations of other scholars about my issue (with whom I disagree on some points); thirdly, I will develop in detail my own interpretation; finally I will make some criticism of the interpretations of the second point and I will draw some conclusions.